The Transformative Potential of School-Based Learning for Preservice Teachers at a University of Technology - Puleng HLASHWAYO; Luzaan SCHLEBUSCH (Social Sciences and Education Research Review)
This qualitative study explored the transformative potential of school-based learning for preservice teachers at a university of technology in the Free State province of South Africa. Preservice teacher education programs globally face the ongoing challenge of effectively bridging theoretical learning with practical classroom experience. Grounded in transformative learning theory, the research employed semi-structured interviews and focus group discussions with 15 purposefully selected third-year Bachelor of Education students specialising in being trained to teach in the Further Education and Training (FET) phase (Grade 10-12). The findings reveal significant shifts in preservice teachers' beliefs about teaching, illustrating a movement from idealistic views rooted in theoretical knowledge to a more nuanced understanding shaped by practical classroom experience. Participants highlighted diverse school contexts as sources of both challenges, such as resource limitations and opportunities for innovation and adaptability in teaching practices. These experiences were pivotal in developing a professional identity and commitment to social justice in education. The study concludes with the critical need for teacher education programs to prioritise robust, contextualised school-based experiences, suggesting that such transformative training can better equip preservice teachers to meet the diverse needs of learners and navigate the complexities of the South African education system. The implications extend to curriculum development and mentoring practices, which require re-evaluation to enhance educational outcomes in Southern Africa.